Means of Influencing the Witness - bin Saleh , Ahmed; Jadallah , Hisham; Shakaterh, Rafat (Journal of Legal Sciences, 2025)
This research aims to explore and analyze the means of influence that a witness may be exposed to in the Sultanate of Oman, and their potential impact on the validity and credibility of testimony before the courts. The study begins by clarifying the legal status of testimony as an important means of proof in the Omani Evidence Law (Royal Decree No. 68/2008), with reference to the conditions and procedures regulating the performance of testimony, such as the obligation for a witness to ally and perform testimony in private. The research also addresses types of influence that may include pressure, threats, or even factors that influence a witness’s recollection or understanding of the incident. The study highlights the importance of witness protection, noting that the Omani legislator has addressed some criminal measures related to witness protection, but recommends the necessity of issuing an independent law or amending the Code of Criminal Procedure to ensure the provision of comprehensive and effective procedural (formal) protection, including means of protecting the identity of the witness and ensuring his safety, to enable him to testify with complete freedom and without fear, which enhances the achievement of justice.